Transient islet-antigen 2 positivity at diagnosis of diabetes during COVID-19 infection in an adolescent with a NEUROD1 variant: a case report - Jennifer K. Yee; Seerat Anand; Juan C. Sanabria; Catherine S. Mao (Journal of Medical Case Reports)
Abstract Background Increased incidence of type 1 and type 2 diabetes has been reported in association with the coronavirus disease 2019 pandemic. Little is known about the impact of coronavirus disease 2019 on the presentation of monogenic forms of diabetes. This case report describes diagnosis of the uncommon maturity onset diabetes of the young (neurogenic differentiation factor 1-maturity-onset diabetes of the young) after transient autoimmunity during coronavirus disease 2019 infection. Case presentation A 19-year-old Mexican male with autism spectrum disorder was diagnosed with diabetes without ketoacidosis during metabolic screening laboratory testing. He tested positive for coronavirus disease 2019 with no respiratory symptoms. His hemoglobin A1c was 14.2%, and had elevated islet-antigen 2 antibody. His blood glucose responded rapidly to initial dietary reduction in carbohydrate intake without insulin initiation, with subsequent improvement in hemoglobin A1c to 7.4% 2 months later. Then, 2 years after diagnosis, his hemoglobin A1c was 6.0%, and repeat antibody testing was negative. He was taking lisinopril for microalbuminuria, but required no medications for glucose control. Genetic testing identified a variant of NEUR OD 1 c.514C > T, p.(Leu172Phe). His mother who was subsequently diagnosed with diabetes, underwent targeted variant testing and was found to have the same neurogenic differentiation factor 1 variant. Conclusions Coronavirus disease 2019 possibly triggered transient autoimmunity, leading to the diagnosis of neurogenic differentiation factor 1-maturity-onset diabetes of the young diabetes. This is also the first description of the clinical features associated with this particular neurogenic differentiation factor 1 variant.